Development Guidelines for Chalong Temple for Religious Tourism: A Case Study of Moo 1, Ban Chalong, Chalong Subdistrict, Thalang District, Phuket Province - Panyaboon, Rachroat; Numbuddee, Phramaha Phanuvich (Journal of Dhamma for Life, 2024)
Development of Wat Choeng Thale for Religious Tourism: A Case Study of Moo 1, Ban Choeng Thale, Choeng Thale Subdistrict, Thalang District, Phuket Province aims to assess the potential of religious tourism at Wat Choeng Thale and to explore guidelines for its development. Data were collected using a questionnaire from 400 participants and interviews with 10 individuals. The research findings revealed that the potential for developing Wat Choeng Thale for religious tourism can be categorized into five aspects as follows: 1. Tourist Attraction: The overall potential in this aspect was found to be at the highest level (𝑥̅=4.64). Specifically, the temple’s natural beauty and favorable climate were rated the highest. 2.Tourism Activities: The overall potential in this aspect was high (𝑥̅=4.34), with recreational activities being the most prominent. 3.Facilities: The overall potential in this aspect was also high (𝑥̅=4.39), particularly regarding the adequacy of parking spaces. 4.Accessibility: The overall potential in this aspect was high (𝑥̅=4.42), with convenience in exploring the various sites within the temple being noted. 5. Accommodation: The overall potential in this aspect was high (𝑥̅=4.44), with reasonable and worthwhile accommodation prices being highlighted. The development guidelines for Wat Choeng Thale for religious tourism include five aspects: 1. Tourist Attraction: It is recommended to manage the opening and closing times of the temple to accommodate tourists wishing to pay respects to the principal Buddha image. 2.Tourism Activities: The temple should have personnel providing historical knowledge and activities that promote tourism within the temple. 3.Facilities: Adequate parking spaces should be allocated, and signs indicating various locations within the temple should be provided. 4. Accessibility: Signs indicating the distance to Wat Choeng Thale should be placed before reaching the temple to attract tourists. 5. Accommodation: Safety is the primary concern for tourists when choosing accommodation, followed by the convenience of travel routes.